A Study on Customer Satisfaction Towards Pradhan Mantri Suraksha Bima Yojana in Tiruchirapplli District - W. Roselin Prabha; C. Paramasivan (Academic Bright Collaboration, 2026)
In India, a large proportion of India ‘s population is without insurance of any kind, that is health, accident or life. In order to facilitate penetration of insurance to the lower income and unorganized employee, government of India launched innovative term insurance scheme namely Pradhan Mantri Suraksha Bima Yojana(PMSBY) on 09 may ,2015 from Kolkata with the motto of “Jan Dhan se Jan suraksha” Social inclusion through financial inclusion .the primary motto of these schemes is to creating a universal social insurance system, targeted especially for the poor and the under-privileged people.it found that social insurance scheme performance, extending the risk coverage temporary sickness benefits in addition to the existing coverage, offering concessional premium amount to existing policy holders to renew their policy, will definitely attract many people and increase the insurance penetration rate.